Customer Centric Strategy - Shields, Kerri (Open textbook library., 2021)
Customer centricity is about organizational transformation making the customer the focus for business decisions, processes, product development, services, and procedures. Some companies purport to be customer centric but they fall short in connecting this concept throughout all functional areas of the business. While it is important to offer superb customer service, being customer centric is far more than that. It's about mapping the customer journey to discover customer needs and wants, what's working and what is not, then taking action to improve the customer experience. Customer loyalty is built through providing exceptional customer experiences. This in turn increases revenues through positive company image, referrals, and increased customer lifetime value. Most organizations today realize that they must focus on the customer to remain competitive.